Acid-base blended membrane for proton exchange membrane fuel cell and preparation method thereof

By introducing acidic organic polymers into proton exchange membrane fuel cells, the acid-base blended membrane is prepared, which solves the problem of easy degradation of Nafion membrane at high temperatures, improves the proton conductivity and mechanical properties of the membrane, and reduces costs.

CN115395067BActive Publication Date: 2025-04-18ZHONGBEI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211028377.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-25
Publication Date
2025-04-18
Estimated Expiration
2042-08-25

AI Technical Summary

Technical Problem

In existing proton exchange membrane fuel cells, the Nafion membrane is prone to degradation at high temperatures, resulting in reduced proton conductivity and gas barrier properties, and at the same time, the cost is high, which limits its large-scale application.

Method used

By introducing acidic organic polymers into the alkaline organic polymer, an acid-base blended membrane of 85-95 wt% basic organic polymer PNBN and 5-15 wt% acidic organic polymer SPI was prepared to improve the proton conductivity and mechanical properties of the proton exchange membrane.

Benefits of technology

High proton conductivity at low ion exchange capacity is achieved, the battery performance of fuel cells is ensured, and the production cost of membrane materials is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115395067B_ABST
    Figure CN115395067B_ABST
Patent Text Reader

Abstract

The invention discloses an acid-base blended membrane for a proton exchange membrane fuel cell, which is prepared by blending 85-95wt% of an alkaline organic polymer PNBN and 5-15wt% of an acidic organic polymer SPI. The invention introduces an acidic organic polymer into the alkaline organic polymer, thereby meeting the requirements of the proton exchange membrane fuel cell for the proton exchange membrane under the premise of reducing the production cost of the membrane material. The acidic organic polymer is used as the proton exchange membrane of the fuel cell, thereby improving the good proton conductivity of the proton exchange membrane at a low ion exchange capacity and ensuring a certain battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane material preparation, and relates to an acid-base blended membrane, in particular to an acid-base blended membrane for a proton exchange membrane fuel cell, and a preparation method of the acid-base blended membrane. Background Art

[0002] A fuel cell is an electrochemical energy conversion device that can directly convert the chemical energy of reactants into electrical energy. As global environmental and energy issues become increasingly serious, new energy sources are urgently needed to be developed. Fuel cells have been proven to have the ability to efficiently convert traditional fossil fuel energy into electrical energy due to their low or zero emissions.

[0003] According to the operating temperature, battery components and the type of electrolyte used in the fuel cell, it can be divided into proton exchange membrane fuel cells (PEMFC), alkaline electrolyte fuel cells (AMFC), molten carbonate fuel cells (MCFC), phosphoric acid fuel cells (PAFC) and solid oxide fuel cells (SOFC). Among them, PEMFC uses hydrogen and oxygen as fuels. Due to its advantages of environmental protection, easy availability of raw materials and high energy efficiency, it has been widely used in aerospace, new energy vehicles, small electronic equipment and other fields.

[0004] Proton exchange membrane is the core component of PEMFC, which plays the role of conducting protons and preventing gas permeation in fuel cells.

[0005] Perfluorosulfonic acid membrane Nafion is currently the most widely used proton exchange membrane, with good mechanical properties and chemical stability, high proton conductivity at low temperatures, and large current density. However, this membrane is easily degraded at high temperatures, resulting in a decrease in its proton conductivity and gas permeation resistance, and its cost is very high, which limits the large-scale application of Nafion membrane in the field of fuel cells. Therefore, the development of low-cost, high-performance proton exchange membranes is an urgent task to be solved in the PEMFC field.

[0006] CN 112216854A discloses an acid-base blended membrane for a fuel cell and a preparation method thereof, wherein a polymer monomer is prepared from nadic anhydride and hexamethylenediamine, and then a randomly polymerized alkaline organic polymer is obtained by ring-opening metathesis polymerization with norbornene, and then mixed with Nafion resin to obtain an acid-base blended membrane having a high ion conductivity at high temperature, and the membrane cost is reduced by replacing the Nafion resin with a part of the alkaline organic polymer. However, the amount of the alkaline organic polymer used in the acid-base blended membrane can only reach 10wt% at most, and not only too many sulfonic acid groups will cause the dimensional stability of the membrane material to decrease, but also the degree of reduction in the membrane cost is limited.

[0007] Therefore, exploring the introduction of a new acidic organic polymer into the above-mentioned alkaline organic polymer is an effective method for preparing low-cost, high-performance acid-base blend membranes. Summary of the invention

[0008] The purpose of the present invention is to provide an acid-base blended membrane for a proton exchange membrane fuel cell and a preparation method thereof, by introducing an acidic organic polymer into an alkaline organic polymer, the proton conductivity of the proton exchange membrane is improved at a low ion exchange capacity, and a certain battery performance is guaranteed.

[0009] The acid-base blended membrane for proton exchange membrane fuel cells of the present invention is prepared by blending 85-95wt% of alkaline organic polymer PNBN and 5-15wt% of acidic organic polymer SPI.

[0010] The alkaline organic polymer PNBN is a random polymer having a structure shown in the following formula (I) and a number average molecular weight of 160,000-180,000.

[0011]

[0012] In the basic organic polymer PNBN, the molar ratio of the two repeating units is p:q = 1:(1.5-2).

[0013] The acidic organic polymer SPI is a random polymer having a structure shown in the following formula (II) and a number average molecular weight of 100,000-150,000.

[0014]

[0015] In the acidic organic polymer SPI, the molar ratio of the two repeating units is m:n = 1:(0.5-1.5).

[0016] Specifically, the acid-base blended membrane for proton exchange membrane fuel cells of the present invention has a structure represented by the following structural formula (III).

[0017]

[0018] Furthermore, the present invention also provides a method for preparing the acid-base blended membrane for the proton exchange membrane fuel cell, which comprises dissolving the alkaline organic polymer PNBN with the structure represented by the formula (I) in dichloromethane to obtain an alkaline organic polymer solution, dissolving the acidic organic polymer SPI with the structure represented by the formula (II) in N,N-dimethylformamide to obtain an acidic organic polymer solution, and then mixing the two solutions to obtain a mixed solution, using the mixed solution to cast a membrane, and forming an acid-base blended membrane after drying.

[0019] It should be noted that the above-mentioned method provided by the present invention is a typical method for preparing the acid-base blend film, but it is not the only method.

[0020] More specifically, the present invention is to mix the alkaline organic polymer solution and the acidic organic polymer solution, stir at room temperature for 2-3 hours, perform ultrasonic treatment for 10-30 minutes, and finally stand for 10-30 minutes to obtain a mixed solution.

[0021] The drying process for preparing the acid-base blended film of the present invention is preferably vacuum drying at 30-40° C. for 2-3 hours, and then heating to 80-100° C. for vacuum drying for 12-15 hours.

[0022] The acid-base blended membrane for proton exchange membrane fuel cells prepared in the present invention is a brown film, insoluble in water, stable in physical and chemical properties, able to meet the requirements of proton exchange membrane fuel cells for proton exchange membranes, and can be used as a proton exchange membrane for fuel cells.

[0023] In the raw materials for preparing the acid-base blended membrane for the proton exchange membrane fuel cell of the present invention, the alkaline organic polymer PNBN can be prepared according to the method provided in CN 112216854A with norbornene diacid anhydride and 1,6-hexanediamine as raw materials to obtain a polymer monomer, and then the polymer monomer and norbornene are subjected to ring-opening metathesis polymerization under the catalytic action of Grubbs 3rd catalyst to prepare a high molecular polymer with norbornene structure as the main body.

[0024] The ring-opening metathesis polymerization reaction of the alkaline organic polymer needs to be carried out in an inert atmosphere and a dry dichloromethane solution.

[0025] In the raw materials for preparing the acid-base blended membrane for proton exchange membrane fuel cells of the present invention, the acidic organic polymer SPI can be prepared according to the method provided in CN 114437347A by reacting 4,4'-diamino-2,2'-disulfonic acid biphenyl and 4,4'-diaminodiphenyl ether with 1,2,4,5-cyclohexanetetracarboxylic dianhydride to obtain a prepolymer solution, and then the two prepolymer solutions are mixed to carry out polymerization reaction to prepare a random polymer.

[0026] The acid-base blended membrane material prepared by the present invention uses a norbornene-based alkaline organic polymer as a matrix and is blended with a sulfonated polyimide-based acidic organic polymer. The preparation method is simple and, compared with the commercial Nafion membrane, the production cost of the membrane material is greatly reduced, thereby correspondingly reducing the cost of the proton exchange membrane fuel cell, which has obvious advantages.

[0027] Furthermore, compared with a single alkaline organic polymer membrane, the acid-base blend membrane has a higher ion exchange capacity. The introduced acidic organic polymer contains sulfonic acid functional groups, which can serve as proton transfer sites and undertake the task of conducting protons.

[0028] Compared with a single alkaline organic polymer membrane, the acid-base blend membrane also has better mechanical properties. The introduced acidic organic polymer has a rigid main chain and contains sulfonic acid groups that can interact with the alkaline groups in the alkaline organic polymer to form a hydrogen bond network. The simultaneous action of these two factors improves the mechanical stability of the membrane material.

[0029] Compared with single alkaline organic polymer membrane, acid-base blend membrane has higher ionic conductivity and is more obviously affected by temperature.

[0030] The CCM method was used to prepare a membrane electrode using the acid-base blended membrane prepared in the present invention, and the membrane electrode was used for testing in a proton exchange membrane fuel cell. The results showed that a higher open circuit voltage and excellent power density were obtained, indicating that the acid-base blended membrane has good gas permeation barrier capability and proton conduction capability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is the infrared spectra of the alkaline organic polymer film and the acid-base blend film containing different mass fractions of acidic organic polymers.

[0032] Figure 2 It is a surface and cross-sectional microscopic morphology of alkaline organic polymer membranes and acid-base blend membranes containing different mass fractions of acidic organic polymers.

[0033] Figure 3 It is the tensile strength and elongation at break of alkaline organic polymer membranes and acid-base blend membranes containing different mass fractions of acidic organic polymers.

[0034] Figure 4 It is the water absorption rate, swelling rate and ion exchange capacity of alkaline organic polymer membrane and acid-base blend membrane containing different mass fractions of acidic organic polymer.

[0035] Figure 5 It is a graph showing the relationship between the ionic conductivity and temperature of the alkaline organic polymer membrane and the acid-base blend membrane containing different mass fractions of acidic organic polymers.

[0036] Figure 6 It is the open circuit voltage and power density of alkaline organic polymer membrane and acid-base blend membrane containing different mass fractions of acidic organic polymer in proton exchange membrane fuel cell at different current densities. DETAILED DESCRIPTION

[0037] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0038] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Those skilled in the art can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0039] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.

[0040] Example 1.

[0041] Weigh 5 g of nadic anhydride and completely dissolve it in 40 ml of acetic acid, then add 10.63 g of 1,6-hexanediamine, and react at 125-130° C. for 3 h under Ar gas protection to obtain a yellow transparent solution.

[0042] After the reaction solution was cooled to room temperature, 40 ml of dichloromethane and 40 ml of deionized water were added, shaken for thorough extraction, and the lower organic layer was collected and washed twice with deionized water to obtain a light yellow transparent solution.

[0043] The pH value of the light yellow transparent solution was adjusted to weak alkalinity with 1 M NaOH solution, and then washed three times with 40 ml of deionized water, dried over anhydrous Na2SO4, and purified by column chromatography to obtain a light yellow oily polymer monomer.

[0044] Weigh 0.2712g of polymer monomer, 0.1946g of norbornene monomer, and 0.0090g of Grubbs catalyst respectively, and dissolve each in 5ml of dry dichloromethane. First, add the polymer monomer and norbornene monomer into the reactor, degas three times, then add the Grubbs catalyst, continue to degas three times, react in an Ar gas atmosphere at 30-40°C for 0.5h, and after the reaction is completed, prepare a basic polymer PNBN solution.

[0045] Example 2.

[0046] Weigh 0.40 g of 1,2,4,5-cyclohexanetetracarboxylic dianhydride and 0.66 g of 4,4'-diamino-2,2'-disulfonic acid biphenyl in a flask, add 10 ml of m-cresol under Ar atmosphere, and after complete dissolution, add 5 ml of toluene and 0.5 ml of isoquinoline, react at 70-80° C. for 5 h and at 180° C. for 18 h to obtain a first prepolymerization solution.

[0047] Weigh 0.25 g of 1,2,4,5-cyclohexanetetracarboxylic dianhydride and 0.25 g of 4,4'-diaminodiphenyl ether into a flask, add 10 ml of m-cresol under Ar atmosphere and completely dissolve, add 0.5 ml of toluene and 0.5 ml of isoquinoline, react at 70-80° C. for 5 h and at 180° C. for 18 h to obtain a second prepolymerization solution.

[0048] The first prepolymerization solution and the second prepolymerization solution were mixed, reacted at 175-185° C. for 18 hours to obtain a random polymer solution, which was poured into 400 ml of ethyl acetate to precipitate a light yellow solid, thereby preparing an acidic polymer SPI.

[0049] Example 3.

[0050] A PNBN solution was prepared according to the method of Example 1 and directly cast to prepare a basic polymer membrane free of acidic polymer.

[0051] Example 4.

[0052] 0.0245 g of SPI was weighed and added into 5 ml of N,N-dimethylformamide to fully dissolve to form a red transparent solution, which was mixed with the PNBN solution prepared in Example 1 and stirred for 2 h, then ultrasonicated for 15 min and allowed to stand for 10 min to prepare a PNBN / SPI blend solution.

[0053] The above blended solution was cast into a clean and flat glass dish by solution casting, dried at 30°C for 3 h and at 100°C for 12 h, and after cooling, an acid-base blended film with an acid polymer mass fraction of 5% was prepared.

[0054] Example 5.

[0055] 0.2434 g of polymerization monomer and 0.1757 g of norbornene monomer were weighed, and a basic polymer PNBN solution was prepared according to the method of Example 1.

[0056] 0.0465 g of SPI was weighed and mixed with the above PNBN solution by casting according to the method of Example 3 to prepare an acid-base blended membrane with an acidic polymer mass fraction of 10%.

[0057] Example 6.

[0058] 0.2426 g of polymerization monomer and 0.1838 g of norbornene monomer were weighed, and a basic polymer PNBN solution was prepared according to the method of Example 1.

[0059] 0.0735 g of SPI was weighed and mixed with the above PNBN solution by casting according to the method of Example 3 to prepare an acid-base blended membrane with an acidic polymer mass fraction of 15%.

[0060] Figure 1 The infrared absorption spectra of the membrane materials prepared in Examples 3, 4 and 5 are given. -1 and 2935cm -1 The absorption peak at 1552 cm represents the CH stretching vibration of the methylene group (-CH2-) in the PNBN matrix. -1 and 1400cm -1 The absorption peak at 1249 cm is attributed to the NH stretching vibration in the PNBN matrix. In the infrared spectra of PNBN / SPI-5% and PNBN / SPI-10%, there is a characteristic absorption peak of sulfonic acid functional group at 1249 cm -1 (O=S=O asymmetric stretching vibration), 1088cm -1 (O=S=O symmetric stretching vibration) and 1018cm -1 (S=O stretching vibration), while these absorption peaks do not exist in PNBN / SPI-0%, indicating that the acidic organic polymer SPI was successfully introduced into PNBN.

[0061] Figure 2 The surface and cross-sectional scanning electron microscope (SEM) images of the membrane materials prepared in Examples 3-6 are given. Figure 2 As shown in (a) and (e), the PNBN / SPI-0% membrane material has a single component, and the surface and cross-section of the membrane are compact and smooth, indicating that the membrane material has a uniform microscopic morphology. Figure 2 (b) and (f), (c) and (g), (d) and (h) correspond to the surface and cross-sectional microstructures of 5%, 10% and 15% membrane materials, respectively. It can be seen that there is no obvious phase separation, indicating that the membrane material is uniform in texture. This can be attributed to the interaction between the two functional groups of SPI containing hydrophilic groups -SO3H and PNBN containing -NH2, thus showing good compatibility. In summary, the SEM results show that PNBN and SPI are mixed uniformly.

[0062] Figure 3The dimensional stability and ion exchange capacity test results of the membrane materials prepared in Examples 3-6. The water absorption rate (WU) and swelling rate (SR) of the PNBN / SPI-0% membrane are the lowest. With the addition of SPI, the WU and SR of the membrane show an increasing trend. This is mainly because the sulfonic acid groups introduced by the SPI polymer are water-absorbing groups, which promote the water absorption and swelling of the membrane material. When the SPI content increases from 5% to 10%, the increase in SR is not as obvious as WU. This is because although the introduced sulfonic acid groups increase, the sulfonic acid groups interact with the matrix with amino groups, and the hydrogen bonds formed help the membrane material to maintain a stable state. In the process of swelling of the membrane material, the hydrogen bonds formed between the amphiphilic groups play a major role. The ion exchange capacity (IEC) of the membrane material also increases with the increase in the introduction of acidic organic polymers, which is mainly the direct effect of the increase in the number of sulfonic acid functional groups. Therefore, the introduction of SPI in the PNBN matrix can effectively improve the stability and ion exchange capacity of the membrane material.

[0063] Figure 4 The mechanical properties of the membrane materials of Examples 3-6. In fuel cells, membrane materials are subject to external environmental effects such as tension and compression. In order to ensure the stable operation of fuel cells, appropriate mechanical properties are the properties that membrane materials must possess. The tensile strength of PNBN / SPI increases with the increase of SPI, while the elongation at break shows an opposite trend. These two opposite trends may be due to the fact that the rigid main chain of SPI introduced by the blending improves the mechanical properties of the blended membrane. On the other hand, the cross-linked structure between the sulfonic acid functional group and the nitrogen-containing group increases, so the more SPI there is in the blended membrane, the tighter the microstructure of the blended membrane. Overall, the prepared blended membrane with the addition of SPI can meet the needs of proton exchange membrane fuel cells (PEMFC).

[0064] Figure 5 Table 1 shows the ionic conductivity (σ) test results of Examples 3-6. The σ of the prepared blended membranes was tested at 20, 40, 60, and 80°C, respectively. The results are as follows: Figure 5 As shown. The results show that the ionic conductivity of the membrane without SPI is the lowest, while the σ of the membrane increases with the increase of the SPI ratio. This can be attributed to the fact that the introduction of SPI provides more proton transfer sites and a hydrogen bond network formed by the acid-base functional groups contained in the two polymers, which allows better proton transfer, and they conform to the Vehicle and Grotthuss mechanisms, respectively. At the same time, the results in Table 1 show that the higher the temperature, the higher the ionic conductivity of the blended membrane. It can be seen from the results that the conductivity of the membrane containing SPI is relatively greatly affected by temperature, mainly because the polymer molecules move faster with increasing temperature, thereby accelerating the transfer of protons. Therefore, the introduction of SPI into the PNBN matrix can effectively improve the electrochemical properties of the membrane material.

[0065]

[0066] Figure 6 The battery performance of the membrane materials prepared in Examples 3, 5 and 6 is shown. The open circuit voltage (OCV) of the PNBN / SPI-0%, PNBN / SPI-10%, and PNBN / SPI-15% membranes is greater than 0.90 V, which indicates that the prepared polymer blends have a high hydrogen permeability. As the SPI ratio increases from 10% to 15%, the power density of the PNBN / SPI membrane is improved, which is due to the -SO3 - Electrostatic interaction with -NH2 of PNBN. Power density with PNBN is 11.8 mW cm -2 In comparison, PNBN / SPI-15% has better compatibility and higher power density, reaching 104.3mW cm -2 Compared with commercial Nafion membrane materials, the membrane materials prepared by the present invention have lower costs on the one hand, and on the other hand, the membrane materials prepared by the present invention can show better battery performance at lower ion conductivity. Therefore, PNBN / SPI blended membrane is a very promising polymer material in PEMFC membrane.

[0067] The above characterization results generally show that compared with PNBN / SPI-0%, the acid-base blended membrane can effectively solve the balance problem between electrochemical performance and dimensional stability due to the electrostatic interaction between the acid and base groups. Therefore, it can be seen that the electrochemical performance of Examples 5 and 6 is significantly better than that of pure alkaline organic polymer membranes, specifically, their power density is significantly higher than that of pure alkaline organic polymer membranes.

[0068] The open circuit voltage of the acid-base blended membrane material prepared by the present invention can reach 0.90V, which is slightly larger than that of other blended membranes, indicating that the membrane material of the present invention can better prevent gas cross contamination. At the same time, at a lower ion exchange capacity, it can still reach 104.3mW cm -2 The power density is high and the electrochemical performance is good, thus achieving the technical effect of the present invention.

[0069] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. An acid-base blend membrane for a proton exchange membrane fuel cell is prepared by blending 85-95wt% of a basic organic polymer PNBN and 5-15wt% of an acidic organic polymer SPI. in, The alkaline organic polymer PNBN is a random polymer having a structure represented by the following formula (I) and a number average molecular weight of 160,000-180,000: In the basic organic polymer PNBN, the molar ratio of the two repeating units is p:q = 1:(1.5-2); The acidic organic polymer SPI is a random polymer having a structure represented by the following formula (II) and a number average molecular weight of 100,000-150,000: In the acidic organic polymer SPI, the molar ratio of the two repeating units is m:n = 1:(0.5-1.5).

2. The acid-base blended membrane for proton exchange membrane fuel cells according to claim 1 has a structure represented by the following structural formula (III): 。 3. The method for preparing the acid-base blended membrane for proton exchange membrane fuel cells according to claim 1 is to dissolve the alkaline organic polymer PNBN with the structure represented by formula (I) in dichloromethane to obtain an alkaline organic polymer solution, dissolve the acidic organic polymer SPI with the structure represented by formula (II) in N,N-dimethylformamide to obtain an acidic organic polymer solution, mix the two solutions to obtain a mixed solution, use the mixed solution to cast a membrane, and form an acid-base blended membrane after drying.

4. The preparation method according to claim 3, characterized in that The alkaline organic polymer solution and the acidic organic polymer solution are mixed, stirred at room temperature for 2-3 hours, ultrasonically treated for 10-30 minutes, and finally allowed to stand for 10-30 minutes to obtain a mixed solution.

5. The preparation method according to claim 3, characterized in that The acid-base blended film is dried at 30-40° C. in vacuum for 2-3 hours, and then heated to 80-100° C. in vacuum for 12-15 hours.

6. Use of the acid-base blended membrane for proton exchange membrane fuel cells according to claim 1 as a proton exchange membrane for fuel cells.

Citation Information

Patent Citations

  • Acid-base blended membrane for fuel cell and preparation method thereof

    CN112216854A

  • Block sulfonated polyimide with micropores as well as preparation method and application thereof

    CN114437347A